2021
DOI: 10.7759/cureus.19989
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Resident Procedures in Rural Versus Urban Emergency Departments

Abstract: Background: Rural rotations can be a valuable experience for emergency medicine (EM) residents. To date, there has not been a retrospective cohort study comparing procedures performed at urban versus rural emergency departments (EDs). Objectives: The purpose of this study was to compare procedures performed by EM residents in urban versus rural EDs, with the hypothesis that there will be no significant difference in the procedures performed. Methods: A retrospective cohort study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results of this study can be compared to a recent study by Carey et al., 7 who also compared procedural exposures between academic and rural EDs. Their study showed increased frequency of exposure to procedures in general when residents worked at a large rural ED compared to an academic hospital and similar exposures when working at a small rural ED.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The results of this study can be compared to a recent study by Carey et al., 7 who also compared procedural exposures between academic and rural EDs. Their study showed increased frequency of exposure to procedures in general when residents worked at a large rural ED compared to an academic hospital and similar exposures when working at a small rural ED.…”
Section: Discussionmentioning
confidence: 80%
“…A small study by Wadman et al 6 (five total residents in the study) suggested that residents on a month-long rural rotation saw similar patient volumes to their academic center with significantly increased rates of exposure to fracture/dislocation reductions and pediatric trauma resuscitations. Another study by Carey et al 7 compared resident performance of "simple" and "complex" procedures at academic versus rural EDs and found no significant differences in procedural experiences. Other than these small studies, no other data have been published on this topic to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, smaller hospitals provide invaluable support on the path to becoming a competent surgeon. They offer the opportunity to take on a higher degree of responsibility and develop greater autonomy at an earlier stage of training [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%